2009
DOI: 10.1007/s11239-009-0428-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low molecular weight heparin (dalteparin) on duration and initiation of labour

Abstract: It has recently been reported that women treated with low molecular weight heparin (LMWH) during pregnancy had 3 h shorter duration of delivery. The aim of the present study was to evaluate whether LMWH (dalteparin) affects labour. From January 1996 to December 2005, 217 consecutive pregnancies, out of 34 216 newborn (prevalence 0.6%) that were given thromboprophylaxis with dalteparin (usually 5,000 IU once daily). These 217 consecutive pregnancies were compared to an unselected control group (n = 1,499) of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…To our knowledge, the effect of LMWH on duration of labor has only been investigated in two clinical studies [ 29 , 30 ]. Isma et al found that 104 nulliparous women exposed to the LMWH dalteparin had, compared to 787 untreated women, one hour shorter first stage of labor and a significantly lower risk of prolonged first stage of labor (4.1% vs 8.5%, respectively P = 0.047).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, the effect of LMWH on duration of labor has only been investigated in two clinical studies [ 29 , 30 ]. Isma et al found that 104 nulliparous women exposed to the LMWH dalteparin had, compared to 787 untreated women, one hour shorter first stage of labor and a significantly lower risk of prolonged first stage of labor (4.1% vs 8.5%, respectively P = 0.047).…”
Section: Discussionmentioning
confidence: 99%
“…Isma et al found that 104 nulliparous women exposed to the LMWH dalteparin had, compared to 787 untreated women, one hour shorter first stage of labor and a significantly lower risk of prolonged first stage of labor (4.1% vs 8.5%, respectively P = 0.047). No such relationships were found for parous women [ 29 ]. One of the main differences with our study is that we examined the diagnosis of labor dystocia and not the actual duration of labor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding non‐pregnant diagnosis numbers are I269, I801, I803, I808, I822, I823, or I828, and I260, I269. Some of the participants in this study have previously been presented in studies concerning the effect of dalteparin on the duration of labor (17,18). The Ethics Committee at the University of Gothenburg approved the study.…”
Section: Methodsmentioning
confidence: 99%